Implementasi Kedaulatan Permanen atas Sumber Daya Alam Dalam Aturan Investasi Asing di Aljazair dan Indonesia - Saru Arifin (Jurnal Hukum IUS QUIA IUSTUM, 2018)
Since first coined by the United Nations at the end of 1950’s, the doctrine of permanent sovereignty over  natural  resources  has  experienced  rapid  dynamics  of  development  —  from  those  originally traditionally practiced to the national interests of a country — then developed and intersected various global issues, such as economy, environment, human rights, and climate change. Such doctrine only confirms to the countries of the world about the importance of permanent sovereignty for each country over  its  natural  resources.  However,  the  management  needs  to  pay  attention  to  various  important aspects that intersect with human interests universally and inclusively. This study uses a normative legal method to discuss the implementation of the 1950 state sovereignty doctrine over natural resources in the investment legal system of developing countries such as Africa and also Indonesia, which is actively opening up to local and international investors to improve the national economy for social welfare. The results show that the implementation of UN Resolution on permanent sovereignty of natural resources in  the  practice  of  foreign  investment  in  Algeria  is  limitative,  particularly  towards  strategic  naturalresources. In contrast, the practice of foreign investment in Indonesia is liberal in nature, and even its share ownership can reach one hundred percent.